2007
DOI: 10.1211/jpp.59.5.0015
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of TRPV1 receptors at the central and peripheral nerves in CFA-induced mechanical and thermal hyperalgesia

Abstract: Transient receptor potential vanilloid 1 (TRPV1) antagonists are known to attenuate two typical symptoms of inflammatory hyperalgesia: thermal and mechanical. However, it is not clear whether the sites of participation of TRPV1 for each symptom are different. In this study, we clarified the difference between the site of TRPV1 involvement in both symptoms by analysing the anti-hyperalgesic activity of two kinds of TRPV1 antagonists given locally (i.e. intraplantarly and intrathecally) in rats with CFA (complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 28 publications
6
46
0
3
Order By: Relevance
“…On day 3 after the incision, SB366791 (150 µg) and/or HC-030031 (125 µg) or vehicle was subcutaneously administrated once into the incised sites in a volume of 25 µL using a 27-gauge needle. These doses of SB366791 and HC-030031 were determined from previous reports (Kanai et al 2007;Barabas and Stucky 2013). HHWT, CHWT, or MHWT was defined before and 30, 60, 90, and 120 min after the administration of SB366791, HC-030031, or vehicle as described above.…”
Section: Peripheral Administration Of Trpv1 or Trpa1 Antagonistmentioning
confidence: 99%
“…On day 3 after the incision, SB366791 (150 µg) and/or HC-030031 (125 µg) or vehicle was subcutaneously administrated once into the incised sites in a volume of 25 µL using a 27-gauge needle. These doses of SB366791 and HC-030031 were determined from previous reports (Kanai et al 2007;Barabas and Stucky 2013). HHWT, CHWT, or MHWT was defined before and 30, 60, 90, and 120 min after the administration of SB366791, HC-030031, or vehicle as described above.…”
Section: Peripheral Administration Of Trpv1 or Trpa1 Antagonistmentioning
confidence: 99%
“…We next evaluated whether peripheral inflammation triggers the release of endogenous linoleic acid metabolites in the spinal cord leading to TRPV1-mediated mechanical allodynia. We tested this hypothesis in the CFA model of inflammation since it is dependent upon spinal TRPV1 activity (6,8). Intraplantar injection of CFA resulted in the development of mechanical allodynia in the injected paw 24 h post injection (Fig.…”
Section: Depolarization Of the Spinal Cord Leads To Increased Release Ofmentioning
confidence: 99%
“…Interestingly, the systemic/spinal administration of TRPV1 antagonists blocks inflammation-induced heat hyperalgesia, as well as mechanical allodynia (5)(6). These findings were unexpected since TRPV1 is not activated by mechanical stimuli, suggesting that spinal TRPV1 activation leads to central sensitization to both thermal and mechanical stimuli (7)(8).…”
mentioning
confidence: 98%
“…This receptor can be activated by noxious heat (Ͼ43°C), extracellular acidification, various lipids, and capsaicin (Caterina et al, 1997;Tominaga and Tominaga, 2005). Several studies demonstrated that TRP channel functions are modulated during inflammation (Ji et al, 2002;Kanai et al, 2007;De Schepper et al, 2008). One of the representations of such a modulation is an inflammatory-mediated heat hyperalgesia (Zhuang et al, 2004;Breese et al, 2005).…”
Section: Introductionmentioning
confidence: 99%